2023
DOI: 10.1101/2023.04.26.23289126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human milk feeding and direct breastfeeding improve outcomes for infants with single ventricle congenital heart disease: Propensity score matched analysis of the NPC-QIC registry

Abstract: Background: Infants with single ventricle (SV) congenital heart disease (CHD) undergo three staged surgeries/interventions, with risk for morbidity and mortality. We estimated the effect of human milk (HM) and direct breastfeeding (BF) on outcomes including necrotizing enterocolitis (NEC), infection-related complications, length of stay (LOS), and mortality. Methods: We analyzed the National Pediatric Cardiology Quality Improvement Collaborative registry (2016?2021), examining HM/BF groups during stage 1 (S1P)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…Our findings of associations between direct breastfeeding and higher Bayley-IV scores are unique, as we did not identify any previous studies focused specifically on breastfeeding and neurodevelopmental outcomes in hospitalised infants. However, skin-toskin maternal contact may improve preterm neurodevelopmental outcomes, 19 and direct breastfeeding confers some differential benefits for hospitalised neonates (e.g., improved gut microbiome, 20 reduced sepsis 11 ). It is possible that infants who did not breastfeed were more critically ill.…”
Section: Nutrition and Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of associations between direct breastfeeding and higher Bayley-IV scores are unique, as we did not identify any previous studies focused specifically on breastfeeding and neurodevelopmental outcomes in hospitalised infants. However, skin-toskin maternal contact may improve preterm neurodevelopmental outcomes, 19 and direct breastfeeding confers some differential benefits for hospitalised neonates (e.g., improved gut microbiome, 20 reduced sepsis 11 ). It is possible that infants who did not breastfeed were more critically ill.…”
Section: Nutrition and Neurodevelopmentmentioning
confidence: 99%
“…9 There is limited evidence about human milk and breastfeeding in the context of critical CHD, 10 and relationships between human milk and neurodevelopment for these infants are currently unknown. A recent study 11 of 2491 infants with single ventricle CHD demonstrated that human milk feeding and direct breastfeeding substantially reduced inflammatory diseases known to impact neurodevelopment (e.g., 72% lower necrotising enterocolitis; 93% lower sepsis). To our knowledge, however, no previous study has investigated relationships between human milk/breastfeeding and neurodevelopment for infants with critical CHD.…”
mentioning
confidence: 99%